Pedagogical Technologies in Legal Education: Historical Analysis and Modern Experience - Sagalaeva, Evgenia; Komarevceva, Irina; Landina, Olga; Melnichuk, Marina (International Journal of Engineering and Technology, 2018)
The article is dedicated to research and analysis of the issues of formation and development of pedagogical technologies in legal education. The historical experience of training of legal human resources both in Russia and in foreign countries is investigated. Special attention is paid to the enchiridia of M. Psellus. The theoretical and practical problems that affect the application of pedagogical technologies in legal education at the present stage are analyzed. The potential of problematic training in the context of legal education is revealed. The scientific novelty of the work is that the authors on the basis of studying the history of the formation and development of pedagogical technologies both in Russia and abroad attempted to determine the main trends in the development of this sphere of social relations and to justify the most constructive proposals in order to improve the training of graduate lawyers.Â